Principles of skill training: A case study of coach practices in skill acquisition training - Barkell, J. F.; O'Connor, D. (7th World Congress on Science and Football (WCSF), 2011, 2011)
Recent literature in the area of skill acquisition training has identified a variety of alternate coaching strategies thought to enhance skill learning and overall skill retention. These changes revolve around increasing the amount of contextual interference and variability of the training session and decreasing feedback frequency and utilising more implicit forms of instruction. The aim of this case study was to identify and compare coaching practices at the youth developmental level of football with two other team sports. Methods Premiership winning coaches from Sydney Schoolboy competitions in football, volleyball and basketball participated in this study. All are accredited coaches in their sport, qualified physical education teachers and former professional players. Fifteen training sessions were coded on five categories of coaching practice - scheduling of blocked, serial or random practices (contextual interference), constant or variable practice (variability of training), frequency of feedback, timing of feedback and the nature of feedback. Results and Discussion Random practice and variable training was most commonly used in all 15 training sessions (p<0.01). The football coach scheduled significantly more random practice (52.8%, p<0.01) and had greater variability of practice (67.9%, p<0.01) compared to the other coaches. The football coach gave players feedback on less occasions (22 v 53-55 p<0.01). Timing of the football coach`s feedback showed no significant differences with the other sports, and was evenly distributed between concurrent (51%) and terminal (49%). The football coach used significantly more explicit feedback (91% p<0.01), than implicit feedback. The findings from this study suggest that football coaches at the youth development level are offering more opportunities to train with contextual interference, however knowledge in the area of athlete feedback during skill training could be improved. Conclusion The football coach performed the most random practice, the highest amount of variability and the lowest frequency of feedback. This may be due to the emphasis placed on training variability and the use of small sided and modified games within the FFA coaching curriculum. Coach education courses for all sports would benefit from including more skill learning principles.